Modern Diagnostic and Prognostic Criteria for Thyroid Diseases (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The above literature review allowed us to consider modern methods of diagnosing diseases thyroid gland. The diagnostic capabilities of clinical and anamnestic, laboratory and instrumental methods, which differ in their informative content and invasiveness, were analyzed.